Brutal expropriation, environmental racism and racial capitalism in Nigeria - Cirakoglu, Kayihan; Miapyen, Buhari Shehu; Cirakoglu, Gizem; Aigbiremhon, Jennifer Airiarebhe; Fon, Nguh Nwei Asanga; Lenshie, Nsemba Edward; Adi, Emmanuel (Routledge Journals, Taylor & Francis Ltd, 2023)
Scholars often analyse the Nigerian political economy from class, ethnic, regional, and other analytic perspectives. Racial capitalism is rarely employed to analyse the Nigerian political economy and the endemic identity crises that always lead to hatred, tension, and violent conflicts. Environmental pollution is often not accidental, but deliberate environmental and economic sabotage. This paper sees it as a dimension of environmental racism. Identity manipulation and the crises accompanying it are normal functioning of racial capitalism.
Keywords: Oil; Delta